Strategi Komunitas Kifah Dalam Membangun Dakwah di Kota Padangsidimpuan - Hasibuan, Muhammad Yusup; Ritonga, Anas Habibi; Dianto, Icol (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah UIN Sultan Maulana Hasanuddin Banten, 2026)
This research is motivated by the increasing public demand for a da'wah model that is adaptive, creative, and relevant to the socio-religious dynamics of urban society, thus requiring da'wah communities such as the Kifah Community to formulate da'wah strategies that can reach various levels of society in Padangsidimpuan City. The research method used is a descriptive qualitative approach through direct observation, structured interviews with the chairman, ten administrators, community leaders, former members, and community media documentation as primary and secondary data. Data were analyzed through the stages of information collection, data reduction, presentation, and drawing conclusions. The results show that the Kifah Community develops da'wah strategies through five main channels, namely routine studies, print media, online media, social religious actions, and participation in large-scale religious campaigns. The findings also show variations in community acceptance, ranging from groups that reject, indifferent, to the majority who are enthusiastic about the Kifah da'wah program. In addition, this study identifies two groups of da'wah challenges: internal challenges in the form of a lack of member activity and time conflicts, and external challenges in the form of negative public perception, dynamics between Islamic organizations, and the demands of digital technology development. The research analysis confirms that the success of Kifah's da'wah strategy depends on the consistency of its cadres and the community's ability to adapt to social change. The discussion of this research underscores that community-based da'wah strategies require a collaborative and innovative approach to remain relevant. The final conclusion states that Kifah's da'wah strategy has had a positive impact on strengthening the religious understanding of the community in Padangsidimpuan City.